In Silico Drug Designing Approach for DrimiaIndica of Human TSLP in Allergy and Asthma - Dr.Girija.R; Dr.Aruna.S; Saamanthi M (International Journal of Pharma and Bio Sciences, 2021)
Drimiaindica are stomachic, emmenagogue, anthelmintic, purgative, and alexiteric. They are useful for paralysis, bronchitis, asthma, dropsy, rheumatism, renal calculi, leprosy, skin diseases, headache, diseases of the nose, internal pains, and scabies in indian traditional medicine. This evaluation also suggests that bufadienolides, flavonoids and steroids might be responsible for its bioactive potential. The pro-inflammatory cytokine Thymic Stromal Lymphopoietin (TSLP)is pivotal to the pathophysiology of widespread allergic diseases mediated by type 2 helper T cell (Th2) responses, including asthma and atopic dermatitis. The emergence of human TSLP as a clinical target against asthma calls for maximally harnessing its therapeutic potential via structural and mechanistic considerations. The phenol-2-carboxylic acid, (M8) showed interaction with THE-72, LEU-85, ASP-87. However, it was noted that there is a hydrogen bond between the derivatives of phenol-2-carboxylic acid was potent inhibitor for TSLP.Here we report the development of a new drimiaindicaplantbasedisolated compounds, showing the silico discovery of and efficacy towards asthma activity.